Brand and Logo Creation for Fried Wonton Chips MSMEs - Anwar, Muhamad Syaeful; Verawati, Liesta; Nurhikmah, Nisnaeni (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a critical role in economic growth by creating job opportunities and reducing unemployment. However, in today's competitive market, MSMEs must innovate and develop strong branding strategies to attract consumers and build trust. This study highlights the challenges of fried wonton chips MSMEs, particularly the lack of a brand and logo, which hampers product recognition, marketing efforts, and competitiveness. A community service initiative addressed these issues by providing brand and logo creation using tools like Canva, equipping MSME owners with practical skills to enhance product identity and marketing. Through preparation, implementation, and evaluation stages, the initiative successfully increased awareness about branding's importance and emphasized involving younger generations to leverage technology for design and promotion. These efforts strengthen MSME competitiveness, build consumer trust, and unlock growth opportunities in local and global markets.